Kelayakan Masker Gel Daun Binahong Untuk Perawatan Kulit Wajah - anna rahma; Murni Astuti (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
This study aims to a) analyze how to make binahong and gelatin leaf gel masks for facial skin care, b) analyze the feasibility of binahong and gelatin leaf gel masks judging by the content of flavonoids and vitamin c, c) analyze the feasibility of binahong leaf gel masks and gelatin judging by texture, aroma, and adhesion. This research uses quantitative approach, with experimental research design. The variab1es in this study were free variab1es (x) and bound variab1es (y). This type of data uses primary data with observation data sources, documentation and questionnaires. Data collection techniques are carried out by means of observation, documentation and questionnaires. This study uses questionnaires/ questionnaires. The steps for analyzing data are descriptive analysis techniques and analysis methods. Based on the resu1ts of 1aboratory tests the content of vitamin C contained in binahong leaf gel masks and gelatin amounted to 788 mg, and Positive (+) contains flavonoids. And based on the resu1ts of organoleptic tests, the quality of binahong leaf gel masks and gelatin seen from the texture showed 29% of panelists stated very viscous, 57% expressed viscous, and 14% expressed less viscous. Judging from the aroma of 29% panelists expressed a very distinctive scent binahong leaves, 71% panelists expressed a distinctive scent binahong leaves. Judging from the adhesy of 57% of panelists stated very sticky, 43% stated sticky. And judging from the panelists' liking showed 43% expressed great fondness for binahong and gelatin leaf gel masks, 57% expressed likes on binahong and gelatin leaf gel masks.